Approaching Emptiness: Subjective, Objective and Existential Dimensions - Peteet, John R. (Journal of religion and health, 2011)
Clinicians have lacked a coherent approach to emptiness, which is both a pervasive metaphor for loss, deficiency, or alienation and a frequently cited spiritual goal. We suggest a framework for approaching emptiness that distinguishes among its subjective, objective, and existential dimensions. Clinicians can use psychodynamic and cognitive behavioral approaches to clarify schemas that distort patients' perceptions of others and of themselves, behavioral and relational approaches to help them deal with real deficiency and loss, and spiritually oriented approaches to put these into a larger context.